Tomato Lycopene –A review - Krisna Malay, Kausalyah; Roy, Anitha; Duraisawamy, Revathy; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
Lycopene is a bright red carotene and carotenoid pigment and phytochemical found in tomatoes and other red fruits and vegetables, such as red carrots, red bell peppers, watermelons, and papayas (but not strawberries or cherries). Although lycopene is chemically a carotene, it has no vitamin A activity. Foods that are not red may contain lycopene as well. The antioxidant properties of lycopene are thought to be primarily responsible for its beneficial properties . Data concerning lycopene bioavailability, tissue distribution, metabolism, excretion, and biological actions in experimental animals and humans are beginning to accumulate, although much additional research is necessary. Although promising data from epidemiological, as well as cell culture and animal studies, suggest that lycopene and the consumption of lycopene-containing foods may affect cancer or cardiovascular disease risk, more clinical trial data is needed to support this hypothesis. In addition, future studies are required to understand the mechanism(s) whereby lycopene or its metabolites are proven to possess biological activity in humans.